2011
DOI: 10.1016/j.jrp.2011.02.004
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of the convergent validity of self-control measures

Abstract: There is extraordinary diversity in how the construct of self-control is operationalized in research studies. We meta-analytically examined evidence of convergent validity among executive function, delay of gratification, and self- and informant-report questionnaire measures of self-control. Overall, measures demonstrated moderate convergence (rrandom = .27 [95% CI = .24, .30]; rfixed = .34 [.33, .35], k = 282 samples, N = 33,564 participants), although there was substantial heterogeneity in the observed corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

55
784
3
27

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 863 publications
(869 citation statements)
references
References 64 publications
(77 reference statements)
55
784
3
27
Order By: Relevance
“…But the problem is that the relationship between personal self-control and cognitive self-control may be insignificant (see Nęcka et al, 2012). One important meta-analytical study (Duckworth & Kern, 2011) showed that the intercorrelations among various measures of self-control were rather weak, particularly if executive functions tasks are concerned. So, it seems questionable whether computerized cognitive tasks measuring the level of development of the so-called executive functions, e.g., the Stroop task (1935), the flankers task (Eriksen & Eriksen, 1974), or the antisaccade task (O'Driscoll et al, 1995;Orylska & Racicka, 2014), give us an insight into the level of development of personal self-control, visible in individual behaviour.…”
Section: Measurement Of Self-controlmentioning
confidence: 99%
“…But the problem is that the relationship between personal self-control and cognitive self-control may be insignificant (see Nęcka et al, 2012). One important meta-analytical study (Duckworth & Kern, 2011) showed that the intercorrelations among various measures of self-control were rather weak, particularly if executive functions tasks are concerned. So, it seems questionable whether computerized cognitive tasks measuring the level of development of the so-called executive functions, e.g., the Stroop task (1935), the flankers task (Eriksen & Eriksen, 1974), or the antisaccade task (O'Driscoll et al, 1995;Orylska & Racicka, 2014), give us an insight into the level of development of personal self-control, visible in individual behaviour.…”
Section: Measurement Of Self-controlmentioning
confidence: 99%
“…This approach also allowed us to take into account processes that moderate impulse control in the assessment of SC (Duckworth and Kern, 2011). The first moderating process we considered in this study was coping, since different coping strategies, e.g., cognitive reappraisal/finding meaning in negative events and problem-directed action, are considered to play an important role in affect regulation (Larsen and Prizmic, 2004).…”
Section: Present Studymentioning
confidence: 99%
“…They, too, failed to find correlations in human across delay choice (labeled "discounting") tasks and inhibitory tasks such as go/no-go tasks or the balloon analogue risk task, which is analogous to a delay maintenance task. Duckworth and Kern (2011) found moderate correlations (r = 0.20 − 0.23) with different delay choice tasks but only small correlations (r = 0.07−0.14) with executive function (inhibition tasks). Thus, humans also show task-specific performance for self-control.…”
Section: Discussionmentioning
confidence: 88%